Factors for practising hibah amanah: a study on muslims investor at Amanah Saham Nasional Berhad, Kuala Selangor / Muhammad Zain Adila Othman - Othman, Muhammad Zain Adila (Academy of Contemporary Islamic Studies, 2018)
The purpose of this paper is to investigate the factors for practicing Hibah Amanah among Muslims investor. It examines the relationship between knowledge, life events and services with practicing Hibah Amanah. The paper has used the data from primary data by contributed the questionnaire to 100 of Muslims investor in Amanah Saham Nasional Berhad (ASNB) Kuala Selangor. Besides, the secondary data such as journal and electronic sources were used to getting more information about Hibah. Other than that, the researcher used descriptive statistics on Likert scale questions to measure the agreement of respondents on the question given. The researcher also used frequency analysis to identify the gender, age, marital status, educational level, monthly income of respondents, health status and total assets. In order to get the result of this study, the researcher has used correlation analysis and it showed there are significant relationships between knowledge, life events and services with practicing Hibah Amanah. The reliability analysis also used by researcher to testing the reliable of the items measure and the result indicated all variable in this study were reliable. Based on overall conclusion, knowledge are the most factors with regard for practicing Hibah Amanah.